Bird diversity and abundance in forest fragments and Eucalyptus plantations around an Atlantic forest reserve, Brazil - Marsden, S. J.; Whiffin, M.; Galetti, M. (Kluwer Academic Publ, 2001)
Little of Brazil's remaining Atlantic forest is protected, so it is important to assess how well the region's wildlife can persist in areas/habitats outside reserves. We studied bird diversity and abundance during 546 point counts in the Sooretama/Linhares reserve, 200 point counts in 31 forest fragments (10-150 h), and 50 point counts in < 30-year-old Eucalyptus plantations, within 7 km of the reserve. Only eight bird species were recorded in Eucalyptus, and this impoverishment, as compared to some Eucalyptus plantations elsewhere in Brazil may be a result of intensive clearance of understory vegetation. Species diversity in forest fragments was significantly lower than in the reserve. Twelve, mostly non-forest or edge species, were significantly commoner in the fragments, but nineteen species were frequent in the reserve but rare or absent in forest fragments. These included two Pyrrhura parakeets, a Brotogeris parakeet, a trogon Trogon, a jacamar Galbula, woodpeckers Piculus and Campephilus, Myrmotherula antwrens, and Hemithraupus and Tachyphonus tanagers. Bird species richness at points in forest fragments did not decline with fragment size, distance from the reserve, or forest quality. However, forest in fragments was more heavily degraded than forest within the reserve and poor forest quality may be the cause of declines in some species. Whilst protection of forest within reserves is a priority, management of forest fragments may aid conservation of some threatened species.
Keywords: Atlantic forest; bird abundance; bird diversity; Eucalyptus; forest fragments; habitat quality